The Effect of Transformational Leadership on Employee Performance: The Mediating Role of Job Satisfaction - Dhika Pratama; Ribhan Ribhan; Nova Mardiana (Science and Education Journal (SICEDU), 2026)
This study aims to analyze the effect of transformational leadership on employee performance, with job satisfaction as a mediating variable, among investigators at the Directorate of Enforcement and Investigation, Directorate General of Customs and Excise. Using a descriptive quantitative approach, data were analyzed using LISREL-based Structural Equation Modeling (SEM). The hypothesis testing indicates that transformational leadership has a direct, positive, and significant effect on employee performance (coefficient = 0.56; t-value = 3.41 ≥ 1.96). Furthermore, job satisfaction is proven to significantly act as a mediating variable in bridging the relationship between transformational leadership and investigator performance. This study shows that, the effective implementation of a transformational leadership style not only directly boosts employee work performance but also operates indirectly by strengthening their job satisfaction.